Pregabalin prescription patterns in private clinics in Iraq: a cross-sectional study - Kurji, Hayder Abdulhafedh; Hasan, Ali Khalaf; Abbood, Mohammed Khalid; Ali, Hiba Mohammed (Pharmakeftiki, 2025)
Pregabalin, despite its widespread use across neurology, psychiatry, and primary care, is increasingly recognized for its potential to be misused. Reports have documented rising prescription volumes alongside anecdotal evidence of an expanding illicit market. This study, conducted at private clinics in Diyala, Iraq, between January and December 2024, aimed at evaluating the pregabalin prescribing patterns in Iraqi general practice and at assessing whether its use warrants concern. Pharmacologically, pregabalin exhibits GABA-mimetic properties and may exert direct or indirect effects on the dopaminergic reward pathway. Although its addiction liability at therapeutic doses is considered low, the perception among misusers that pregabalin constitutes a legitimate substitute for illicit substances raises public health concerns. Our study has found that 45% of pregabalin users were aged 60–69 years. Prolonged use (>4 weeks) was observed in 75% of cases and was statistically significant (p<0.001). Insomnia accounted for 43% of prescriptions, also reaching statistical significance (p<0.001). These findings underscore the importance of thorough clinical assessment prior to pregabalin initiation, including evaluation of any history of substance misuse and vigilance for signs of abuse during treatment.